2012
DOI: 10.1063/1.4742915
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of S-branch N2-H2 Raman linewidths using time-resolved pure rotational coherent anti-Stokes Raman spectroscopy

Abstract: S-branch N2-H2 Raman linewidths have been measured in the temperature region 294–1466 K using time-resolved dual-broadband picosecond pure rotational coherent anti-Stokes Raman spectroscopy (RCARS). Data are extracted by mapping the dephasing rates of the CARS signal temporal decay. The J-dependent coherence decays are detected in the time domain by following the individual spectral lines as a function of probe delay. The linewidth data set was employed in spectral fits of N2 RCARS spectra recorded in binary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…14,15 The applicability of the CARS technique has been extended using time-resolved probing to map the dephasing mechanisms for a number of molecules following coherent excitation. [16][17][18][19][20][21] In rotational CARS, mixtures of multiple species yielding a complex spectrum can be simplified as the coherence from the small molecules is significantly longer-lived; thus, an appropriate probe delay can yield simplified spectra. 22,23 One of the long-standing goals in CARS measurements has been the capability to obtain CARS spectra in multiple spatial dimensions simultaneously.…”
mentioning
confidence: 99%
“…14,15 The applicability of the CARS technique has been extended using time-resolved probing to map the dephasing mechanisms for a number of molecules following coherent excitation. [16][17][18][19][20][21] In rotational CARS, mixtures of multiple species yielding a complex spectrum can be simplified as the coherence from the small molecules is significantly longer-lived; thus, an appropriate probe delay can yield simplified spectra. 22,23 One of the long-standing goals in CARS measurements has been the capability to obtain CARS spectra in multiple spatial dimensions simultaneously.…”
mentioning
confidence: 99%
“…At atmospheric pressure, pure rotational CARS from N 2 is well within the pressure limit of the isolated line approximation [12]. Thus, the Raman Lorentzian linewidth (FWHM) is given by (1)…”
mentioning
confidence: 70%
“…In the past, highly resolved measurements in the frequency domain using techniques such as inverse Raman spectroscopy were used to build a database of temperature and pressure-dependent Raman broadening coefficients [5][6][7], and linewidth scaling models were then incorporated into the CARS spectral fitting code to extrapolate to arbitrary temperature and pressure. Recently, ultrafast CARS techniques have been employed to directly measure the collisional dephasing of Raman coherences in the time domain, enabling a rapid measurement of the Raman broadening coefficients for a number of molecules [8][9][10][11][12][13][14]. In these experiments, Raman coherences are excited by the difference frequency between pump and Stokes laser pulses that are picoseconds (ps) or femtoseconds (fs) in duration.…”
mentioning
confidence: 99%
“…18 In the past few years, the time-resolved picosecond (ps) CARS spectroscopic technique has been developed for direct measurements of accurate Raman collisional linewidths. 5,[18][19][20][21] In a previous study, we have shown that ps-duration probe pulses offer an ideal combination of spectral and temporal resolution to provide spectrally resolved, rotational state-selective collisional lifetimes. 19 This time-domain technique therefore allows direct determination of the collisional lifetimes associated with state-resolved molecular transitions, which can be inverted to obtain accurate frequency-domain linewidths.…”
Section: Introductionmentioning
confidence: 99%